Modifikasi Katalis CaO Untuk Produksi Biodiesel Dari Minyak Bekas - Gani Rachim, St. Annisa; Raya, Indah; Zakir, Muhammad (Indonesian Journal of Chemical Research, 2017)
Research about modification of CaO catalyst to produce biodiesel has done. This research aims to know the effectiveness of CaO-ZnCl2 belong to ASTM D6751 to get a yield biodiesel. Modification of the CaO with ZnCl2 was conducted by impregnation method using methanol and n-hexane. For synthesis biodiesel, methanol is used as solvent and Waste Cooking Oil (WCO) as raw material. Ratio molar of WCO and methanol is 12:1 with 3% CaO-ZnCl2 added. This reaction is carried out at a temperature of 65oC. the biodiesel is characterized by Fourier Transform Infrared (FT-IR) to determine the presence of ester groups formed. The yield percentage of biodiesel produced is 77.94%. The characterization of biodiesel properties consist of acid number is 73.38 mg KOH/g, density is 0.9038 and water content is 0.0053%.